Patient-perceived value of Medication Therapy Management (MTM) services: a series of focus groups - Heidi Schultz; Sarah M. Westberg; Djenane Ramalho de Oliveira; Amanda Brummel (University of Minnesota Libraries Publishing, 2012)
Objective: To determine the patient-perceived value of MTM services and non-financial barriers preventing patients with insurance coverage from receiving MTM services. Design: Focus groups. Setting: Fairview Pharmacy Services, Minneapolis, MN. Participants: Three focus groups, each with five to nine participants, consisting of different participant populations: (i) patients who paid out-of-pocket to receive MTM services; (ii) insurance beneficiaries, under which MTM is a covered benefit and participants may have received incentives for receiving MTM services; (iii) patients with an insurance plan which covers MTM services who were recruited to receive MTM services but declined. Intervention: MTM services. Main Outcome Measure: Patient-perceived value of MTM services and non-financial barriers. Results: Seven themes were identified relating to the patient-perceived value of MTM services: collaboration of the health care team, MTM pharmacist as a supporter/advocate/confidant, MTM pharmacist as a resource for questions and education, accessibility to the MTM pharmacist, financial incentives for participation in MTM services, MTM pharmacy as a specialty field, and the MTM pharmacist as a coordinator. Three themes were identified regarding patient-perceived non-financial barriers to receiving MTM services, including: availability of the MTM pharmacist, patient/physician lack of knowledge of MTM services, patient's belief that MTM services are not needed. Conclusion: MTM is a service which patients identify as valuable. Patients are able to identify non-financial barriers that may prevent some patients from receiving MTM services. This study provides preliminary evidence of both the value and barriers perceived by patients.   Type: Original Research